Morphology changes induced by laser irradiation on disperse red 13 films prepared by physical vapor deposition - Silva, J. R.; De Souza, N. C.; Dos Santos, D. S.; De Vicente, F. S.; Marletta, A.; Li, M. Siu; Oliveira, O. N.; Giacometti, J. A. [UNESP] (Elsevier, 2003)
Surface morphology changes induced by argon laser irradiation (514 nm) on disperse red 13 (DR13) films prepared by physical vapor deposition (PVD) were investigated. Atomic force microscopy was used to characterize the irradiated sample for different periods of irradiation. Needle-shape structures are observed which are attributed to the symmetry of DR13 molecules. The film becomes increasingly closely packed with the irradiation, with lower root mean square roughness for long exposure times. This is due to photoisomerization of DR13 molecules and probably heating of the sample, which can provide the required mobility for the molecular rearrangement. The rearrangement is such that voids in the film are filled in upon irradiating the sample, thus decreasing the film roughness and increasing the packing.
Keywords: Atomic force microscopy; Manipulation of surface structure and morphology; Argon; Heating; Isomerization; Morphology; Physical vapor deposition; Thin films; Photoisomerization; Laser beam effects